Influence of International Large-Scale Assessments on National Education Policies - Orechova, Monika (Vilnius University Open Series, 2020)
This article analyzes previous research on the influence of international large-scale assessments (PIRLS, TIMSS, PISA) to national education policies. Based on this meta-analysis, four trajectories of influence are presented and discussed: direct impact, indirect impact via a general education discourse, direct and indirect legitimation.